Forty years of HIV infection and AIDS in Taiwan: Reflection on the past and looking toward the future - Sung-Hsi Huang; Hsun-Yin Huang; Stephane Wen-Wei Ku; Po-Hsien Kuo; Kuan-Yin Lin; Guan-Jhou Chen; Chia-Chi Lee; Yen-Fang Huang; Chien-Ching Hung (Journal of Microbiology, Immunology and Infection)
We review the epidemiology, policies, and control programs of HIV infection in Taiwan in the past 40 years since the first case of HIV infection was diagnosed in 1984. With the introduction of combination antiretroviral therapy (ART) in Taiwan in 1997, the incidences of HIV-related opportunistic illnesses and mortality have significantly declined. However, despite improved access to HIV testing and treatment, late presentation of HIV infection remains common. Unprotected sex, particularly among men who have sex with men, continues to be the leading risk for HIV transmission after implementation of harm reduction program to control an outbreak of HIV infection among people who inject drugs that occurred in 2003–2007. The sequential introduction of well-tolerated, effective, single-tablet antiretroviral regimens has facilitated the implementation of “treat-all” policy in 2016, rapid ART initiation within 7 days of diagnosis in 2018, and same-day ART initiation in 2021 when immunochromatography was used for rapid confirmation of HIV infection. Government-funded pilot program of pre-exposure prophylaxis for HIV infection, which was launched in 2016 followed by wider enrollment of people at high risk for HIV acquisition in 2018, have contributed to sustained declines of the incidence of HIV infection since 2018, along with high rates of linkage to HIV care, ART initiation, viral suppression, and retention in care in Taiwan. Challenges remain to achieve HIV elimination and long-term successful management of HIV infection, which include stigma and discrimination, late presentation of HIV infection, and accelerated ageing with increasing rates of co-morbidities among people with HIV.